Teenage motherhood, education, and labor market outcomes of the mother: Evidence from Brazilian data - Renata Narita; Maria Dolores Montoya Diaz (EconomiA, 2016)
This paper studies the effects of teenage motherhood on later educational and labor market achievement of the mothers. We construct a pseudo panel from the Brazilian Household Surveys (the 1992–2004 PNADs) and from the Health Ministry data (DATASUS 1981–1992) by state of birth and cohort. We find that the effects of teenage pregnancy are much stronger for high school completion and labor market participation than for schooling or wages. A reduction in teenage pregnancy by one standard deviation explains (i) 9.2% of the increase in high school completion and (ii) 5.4% of the increase in women's labor market participation, as observed over 10 cohort years. Lifecycle results show that the gains in terms of high school education are greater for younger than for older women, suggesting that women who give birth as teenagers tend to catch up with high school education while young but not as they become older. The results on labor market participation show persistent teenage motherhood effects. – – Este artigo analisa os efeitos da maternidade na adolescência sobre os níveis de escolaridade e resultados no mercado de trabalho dessas m\~aes. Foi construído um pseudo painel a partir das Pesquisas Nacionais por Amostra de Domicílios (PNADs 1992-2004) e dos dados do Ministério da Saúde (DATASUS 1981-1992) por Estado de nascimento e coorte. Os resultados indicam que os efeitos da gravidez precoce s\~ao muito mais fortes para a conclus\~ao do ensino médio e participaç\~ao no mercado de trabalho do que para anos de estudo ou salários. Um reduç\~ao na gravidez na adolescência de um desvio-padr\~ao explica (i) 9,2% do aumento na conclus\~ao do ensino médio e (ii) 5,4% do aumento na participaç\~ao feminina no mercado de trabalho, como observado ao longo de 10 anos de coortes. Resultados da análise do ciclo de vida mostram que os ganhos em termos de conclus\~ao do ensino médio s\~ao maiores para adolescentes mais jovens do que para as mais velhas, o que sugere que as mulheres que s\~ao m\~aes na adolescência tendem a concluir o ensino médio, quando s\~ao mais jovens, mas n\~ao quando s\~ao mais velhas. Os resultados sobre a participaç\~ao no mercado de trabalho mostram que os efeitos da maternidade na adolescência s\~ao persistentes.
Keywords: O10; O54; J13; J22; 330; Teenage fertility; Education achievement; Female labor supply; Wages; Economic development